Effect of commercial mouthwashes on the corrosion and tribocorrosion behaviour of a Co–Cr dental casting alloy. Issue 3 (26th June 2015) - Pontes, J. R.; Alves, A. C.; Toptan, F.; Galo, R.; Ariza, E.
Abstract : Co–Cr alloys are widely used in fabrication of removable partial dentures, particularly as a dental framework. The micro‐movements between the framework and the teeth or some particles of food in contact with the framework can lead to wear. The present study aimed at studying the influence of the commercial mouthwashes on the corrosion and tribocorrosion behaviour of the Co−Cr dental casting alloy. Corrosion behaviour was investigated in alcohol‐free and alcohol‐containing Listerine® and Colgate Plax® added artificial saliva solutions at body temperature by electrochemical impedance spectroscopy and potentiodynamic polarization tests. Additionally, tribocorrosion tests, performed in selective solutions under open circuit potential, using a reciprocating ball‐on‐plate tribometer, were used to study the combined action of wear and corrosion. Results suggest that the presence of mouthwashes did not affect negatively the corrosion and tribocorrosion behavior of Co‐Cr dental alloy.